Pneumatosis cystoides intestinalis as a pathologic lead point of an ileocolic intussusception: A case report - Teren W.A. Culbertson; David P. Bliss, Jr. (Journal of Pediatric Surgery Case Reports)
Introduction: Ileocolic intussusception is an acute intestinal obstruction that requires prompt diagnosis and treatment. This case presents a rare pathologic lead point for ileocolic intussusception. Case presentation: A nine-year-old female with a history of functional abdominal pain and constipation presented to the emergency department with acute abdominal pain, bilious emesis and one episode of non-bloody diarrhea. Abdominal x-rays were concerning for a bowel obstruction and an abdominal ultrasound showed an intussusception of unclear location. Subsequent abdominal/pelvic computerized tomography scan identified an ileocolic intussusception with pneumatosis cystoides intestinalis (PCI) acting as a pathologic lead point. The patient underwent two air enema reduction procedures that were deemed to be incomplete. As a result, a diagnostic laparoscopy was performed, which confirmed PCI and identified a previously reduced ileocolic intussusception. Post-operatively, she completed a seven-day course of oral metronidazole and had an unmarkable recovery. At a three-week follow-up visit, persistent PCI was present on abdominal radiographs, which resolved after an additional 14-day course of metronidazole. Further outpatient evaluation revealed no other potential lead points other than that of the known PCI. Conclusion: This case highlights the rare occurrence of pneumatosis cystoides intestinalis acting as a pathologic lead point for ileocolic intussusception in a pediatric patient. Ileocolic intussusception should be considered a potential complication for young patients with PCI.